Juridical Review of the Position of Balinese Women in Inheritance from the Perspective of Balinese Customary Law - Made Artha Rimbawa; I Putu Andika Pratama (Journal Equity of Law and Governance, 2025)
Women are legal subjects who are still subject to discriminatory treatment, one of which occurs in the case of inheritance as happened to women in Bali because the inheritance system in Bali uses a patrilineal system. In family law and inheritance where Hindu law emphasizes the rights and obligations of sons with purusha status. So that problems arise related to the position of Balinese women in inheritance matters. The formulation of the problem in this issue is: (1) What is the inheritance status of Balinese women in the perspective of Balinese customary law, and (2) What is the inheritance status of Balinese women in the perspective of Human Rights (HAM). This research is a doctrinal research using primary, secondary and tertiary legal materials. The technique of collecting legal materials is carried out by studying documents using a statue approach, a fact approach, and an analythical conceptual approach. The results of this research are: First, according to Balinese Customary Law, women can receive inheritance or become heirs as long as their marriage status is Purusha. However, in its development, Balinese women are entitled to inheritance based on the Keputusan Pesamuan Agung III MUDP Bali No. 01/Kep/PSM-3MDP Bali/X/2010, 15 October 2010. Second, the Law of the Republic of Indonesia Number 39 Year 1999 concerning Human Rights and the Convention on The Elimination of All from Discrimination Against Women does not regulate whether or whether or not women are heirs or whether or not women are entitled to receive inheritance. So that in this case the determination of whether or not women, especially in Bali, to inherit is focused on the aspect of Balinese Customary Law as a form of recognition of the Customary Law Community Unit which is regulated in the Constitution.